2022
DOI: 10.3390/en15030891
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Building Skin Concept Resulting from a New Bioinspiration Process: Design, Prototyping, and Characterization

Abstract: Building envelopes can manage light, heat gains or losses, and ventilation and, as such, play a key role in the overall building performance. Research has been focusing on increasing their efficiency by proposing dynamic and adaptive systems, meaning that they evolve to best meet the internal and external varying conditions. Living organisms are relevant examples of adaptability as they have evolved, facing extreme conditions while maintaining stable internal conditions for survival. From a framework based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…One of the first studies that utilized the term "adaptive facade" (AF) was [22] in its first edition in 2007 [6]. It has been followed by the concept of the adaptive building envelope in the literature which is defined by different terminologies such as "adaptive building skin" [23], "adaptive building facade" [24], "climate adaptive building envelope" [25] and so forth. "Climate adaptive building shell" was introduced by Loonen et al [26].…”
Section: Solar Adaptive Facadesmentioning
confidence: 99%
“…One of the first studies that utilized the term "adaptive facade" (AF) was [22] in its first edition in 2007 [6]. It has been followed by the concept of the adaptive building envelope in the literature which is defined by different terminologies such as "adaptive building skin" [23], "adaptive building facade" [24], "climate adaptive building envelope" [25] and so forth. "Climate adaptive building shell" was introduced by Loonen et al [26].…”
Section: Solar Adaptive Facadesmentioning
confidence: 99%
“…Building envelope function as a barrier between the distinctive environment of a building, including the resistance to heat, water, air, light, air and noise transfer as declared by Uzair Muhammad et al, [16]. Hubert et al, [19] found that the building envelope is one of the important elements of outer shell of a building to maintain the indoor condition as a dry, heated, or cooled indoor environment and facilitate its climate control. Building envelope is also a key aspect of energyefficient-high performance building, solar gains, air leaks, water leakage, moisture control, and thermal loose and gains are all affected by building envelope design and construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept called Stegos was designed through a interdisciplinary work of engineers, architects, designers in [33]. It was inspired by the radiative properties of two animals: the morpho butterfly, which presents emissive adaptability on its wings to adjust to an increase in body temperature [34]; and the chameleon for its color changes, thermal regulation and camouflage, through the spatial modification of its dermal crystalline network [35].…”
Section: Bio-inspired Conceptmentioning
confidence: 99%
“…An insulation foam was added between the two assemblies to ensure proper contact and no trapped air. Detailed characteristics of the devices and their position can be found in [33].…”
Section: Experimental Set-up and Protocolmentioning
confidence: 99%
See 1 more Smart Citation